A continuum damage mechanics model for 2-D woven oxide/oxide ceramic matrix composites under cyclic thermal shocks. Issue 5 (1st April 2020) - Yang, Zhengmao; Lui, Hui
Abstract: Oxide/oxide-ceramic matrix composites (ox/ox-CMCs) are excellent candidates for material applications in high-temperature and oxidizing environments, which exhibit complex couplings between the thermal and mechanical fields. Uniaxial tensile tests are conducted for 0°/90° and ± 45° fiber orientation of the thermal shocked ox/ox-CMCs. The study reveals that the anisotropy properties of the thermal shocked ox/ox-CMCs result in different degrees of thermomechanical damage, which are reflected in the degeneration of the modulus. Based on the detailed experiments and analysis, a cyclic thermal shock-induced thermomechanical damage model of the 2-D woven ox/ox-CMCs is proposed, incorporating two tensile scalar damage parameters, and one shear scalar damage parameter. The model will contribute to predicting the thermomechanical damage evolution throughout the composite structure under thermal transient conditions. In addition, the model was validated with numerical simulation to demonstrate the damage model performance, which is relatively crucial in damage tolerance analysis in the aeronautical industry. Highlights: The cyclic thermal shocked induced thermo-mechanical damage in ox/ox-CMCs was investigated systematically. Proposed a macroscopic thermo-mechanical damage evolution model of ox/ox-CMCs under cyclic thermal shock. The model can predict the thermomechanical damage evolution of the composite's mechanical throughout the structure. The internal mechanism of thermomechanical damage in ox/ox-CMCs through strain energy was rational physical interpreted.